KOMUNIKASI ANTARPRIBADI PIMPINAN DAN PEGAWAI DALAM MENINGKATKAN MOTIVASI KERJA DI KANTOR DESA DAYUN KABUPATEN SIAK - Boni Sahat Tua; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
A process that will always happen in an institution is a communication process. Through communication process information exchange, ideas and experiences. Communication between leaders and employees must always be honest and built based on trust and open attitude between each other to build spirit dan motivation in work.The purpose of this study to know the openness, empathy, positive behavior, supportive attitude and equality of interpersonal communication of leaders and employees in improving work motivation in the office of Dayun village. This research uses qualitative research method with self disclosure. Subject of research consists of one person leadership, three employees and two people as a supporting informant selected by using purposive sampling technique. This study uses data collection techniques interviews, observation and documentation research.Research results show that (a) openness, leadership and employees always emphasize that every existing and involved line must be open to each other without being covered by each other. (b) empathy, leaders always closer, give attention and feel that is being felt by employees so that employees feel cared for and can improve work motivation. (c) positive behavior, either employees or leaders never arise sespicion. Leaders always apply positive thinking to employees, so that employees can work well and comfortable. (d) supportive attitude, leadership and employees always support each other in any case for the achievement of the goal of providing the best service for community, and (e) equality, the leadership never distinguishes caste any degree between him and his servants. He imposed the same thing to improve work motivation and actieve goals.Keyword : interpersonal communication, work motivation